2012
DOI: 10.1007/s10195-011-0174-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of 32-mm alumina-on-alumina THA for avascular necrosis of the femoral head

Abstract: BackgroundCeramic bearings in total hip arthroplasty (THA) have been introduced in clinical practice to minimize the problem of polyethylene particle–induced osteolysis. The aim of the study is to report the results of 68 consecutive alumina-on-alumina THAs done in 61 patients for avascular necrosis (AVN) of the femoral head.Materials and methodsIn all implants a press-fit cup was used; it was combined with a 32-mm alumina head and with titanium-alloy stems. The mean age at surgery was 50 years. At an average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
7
12
0
Order By: Relevance
“…We found that the mean Harris hip score was 93 points at a mean followup of 6.5 years. Our results were comparable to those in other reports of THA using 32-mm third-generation alumina ceramic-on-ceramic bearings [18,21,30,31]. The mean Harris hip score has ranged from 89 to 97 points at a mean followup of 8.1 years (range, 6.2-12.9 years) ( Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…We found that the mean Harris hip score was 93 points at a mean followup of 6.5 years. Our results were comparable to those in other reports of THA using 32-mm third-generation alumina ceramic-on-ceramic bearings [18,21,30,31]. The mean Harris hip score has ranged from 89 to 97 points at a mean followup of 8.1 years (range, 6.2-12.9 years) ( Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…One study done before 1990 demonstrated that total hip arthroplasty in patients with osteonecrosis had a 17% revision rate at a mean of nine years, while total hip arthroplasties in studies done after 1990 had a 3% revision rate at a mean follow-up of six years 127 . Excellent survivorship at follow-up intervals of greater than ten years suggests that osteonecrosis does not lead to inferior outcomes with modern techniques and implants 273,278,279,285,[287][288][289]292,296,298 . Recent radiostereometric analysis studies have shown low wear rates and excellent survivorship rates at ten years postoperatively [305][306][307] .…”
Section: Total Hip Arthroplastymentioning
confidence: 99%
“…Issa et al [29••] assessed the outcomes in patients with ON who had undergone core decompression (n=19 hips) versus 45) between both cohorts. Therefore, the authors concluded that undergoing a prior core decompression did not negatively impact those who may eventually require THA.…”
Section: Core Decompressionmentioning
confidence: 99%